HPV-related anal cancer is associated with changes in the anorectal microbiome during cancer development - Elnaggar, Jacob H.; Huynh, Victoria O.; Lin, Daniel; Hillman, R. Tyler; Abana, Chike O.; El Alam, Molly B.; Tomasic, Katarina C.; Karpinets, Tatiana V.; Kouzy, Ramez; Phan, Jae L.; Wargo, Jennifer; Holliday, Emma B.; et al. (Frontiers in Immunology, 2023)
Background: Squamous cell carcinoma of the anus (SCCA) is a rare gastrointestinal cancer. Factors associated with progression of HPV infection to anal dysplasia and cancer are unclear and screening guidelines and approaches for anal dysplasia are less clear than for cervical dysplasia. One potential contributing factor is the anorectal microbiome. In this study, we aimed to identify differences in anal microbiome composition in the settings of HPV infection, anal dysplasia, and anal cancer in this rare disease. Methods: Patients were enrolled in two prospective studies. Patients with anal dysplasia were part of a cross-sectional cohort that enrolled women with high-grade lower genital tract dysplasia. Anorectal tumor swabs were prospectively collected from patients with biopsy-confirmed locally advanced SCCA prior to receiving standard-of-care chemoradiotherapy (CRT). Patients with high-grade lower genital tract dysplasia without anal dysplasia were considered high-risk (HR Normal). 16S V4 rRNA Microbiome sequencing was performed for anal swabs. Alpha and Beta Diversity and composition were compared for HR Normal, anal dysplasia, and anal cancer. Results: 60 patients with high-grade lower genital tract dysplasia were initially enrolled. Seven patients had concurrent anal dysplasia and 44 patients were considered HR Normal. Anorectal swabs from 21 patients with localized SCCA were included, sequenced, and analyzed in the study. Analysis of weighted and unweighted UniFrac distances demonstrated significant differences in microbial community composition between anal cancer and HR normal (p=0.018). LEfSe identified that all three groups exhibited differential enrichment of specific taxa. Peptoniphilus (p=0.028), Fusobacteria (p=0.0295), Porphyromonas (p=0.034), and Prevotella (p=0.029) were enriched in anal cancer specimens when compared to HR normal. Conclusion: Although alpha diversity was similar between HR Normal, dysplasia and cancer patients, composition differed significantly between the three groups. Increased anorectal Peptoniphilus, Fusobacteria, Porphyromonas, and Prevotella abundance were associated with anal cancer. These organisms have been reported in various gastrointestinal cancers with roles in facilitating the proinflammatory microenvironment and neoplasia progression. Future work should investigate a potential role of microbiome analysis in screening for anal dysplasia and investigation into potential mechanisms of how these microbial imbalances influence the immune system and anal carcinogenesis.